(untitled) (KULT_online, 2019)
Colonialism and the Jews is a thought-provoking volume examining the intersections of Jewish and colonial history. Looking at Jews as agents and subjects of empires, at their political engagement within imperial systems and at Zionism’s links with colonialism, it is an important reference book for everyone trying to better understand the role of minorities in multinational colonial empires. Articles ranging from studies on Jews in French Morocco to Jewish return migration within the British Empire provide for a broad comparative perspective elucidating how Orientalism, Jewishness, and modernization intertwined within European colonial empires.